Chitosan-alginate porous scaffold incorporated with hydroalcoholic Zingiber officinale Roscoe extract for neural tissue engineering - Hassan Sohrabian Kafraj; Maryam Alipour; Abdolhosein Shiravi; Vida Hojati; Mojtaba Khaksarian (GarVal Editorial Ltda., 2023)
Context: Preparing a suitable substrate for the culture of neural stem cells and their proliferation in neural tissue engineering is of paramount importance. Aims: To evaluate the effect of the hydroalcoholic Zingiber officinale extract incorporated in the chitosan-alginate scaffold (Chi-Alg-Zo) on nerve tissue. Methods: The porous scaffolds developed in the present study were investigated in terms of their surface properties, chemical interaction, crystallinity, thermal stability, porosity percentage, pore sizes, degradability, and water absorption properties. To this end, the following tests were performed: Field emission scanning electron microscope (FE-SEM), Fourier-transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), thermal gravimetric analysis (TGA), porosity based on liquid replacement, Image-J analysis, and water degradation and absorption test. Mouse neural stem/progenitor cells (NS/PCs) were harvested from the embryonic mouse brain. NSCs were seeded on scaffolds incorporated with hydroalcoholic Z. officinale extract. The MTT assay was done for the survival and the proliferation of neural stem/progenitor cells (NS/PCs) on scaffolds. Results: Results indicated the good capacity of Chi-Alg-Zo for proliferation and differentiation into glial (astrocytes and oligodendrocytes) lineages. A suitable surface, which was provided for cellular interaction, led to the advancement of cell survival, connectivity, proliferation, and separation of NSCs. Conclusions: The present study evaluated the separation of stem cells on the scaffold, finding that the expression of the glial fibrillary acidic protein (GFAP) and Oligo4 markers was higher in Chi-Alg scaffolds containing hydroalcoholic Z. officinale extract. Chi-Alg-Zo scaffolds could be suitable candidates for neural tissue engineering.